Evaluasi Tax Diagnostic dan Tax Audit Review Pada PT. X Dalam Rangka Pelaksanaan Tax Efficiency dan Self-Defence atas Pemeriksaan Pajak - Eduardo Samary Parulian; Christine Tjen (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2020)
The high difference of interests between taxpayers who are trying to pay taxes as obediently and efficiently as possible with the state (Tax Officer) who is trying to maximize revenue through taxes certainly has an impact on increasing audits and compliance of taxpayer, one of which is PT. X. This study aims to analyze the effectiveness of the application of Tax Planning namely Tax Diagnostic and Tax Audit Review. This study uses qualitative methods to be able to analyze more deeply about the strategies taken by PT. X in doing taxation efficiency. The results showed that the use of Tax Diagnostic provides PT X information to be able to act efficiently in taxation both administratively or materially, and the use of Tax Audit Review provides PT X information to be able to conduct self-defense (Pre-Audit) in the event of a tax audit by tax officers and increasing company Tax Saving in tax audits that occurred in 2015 to 2016.